Concentração de flúor em águas envasadas: análise laboratorial e da legislação relacionada - Garbin, Clea Adas Saliba [UNESP]; Lima, Arinilson Moreira Chaves [UNESP]; Garbin, Artênio José Isper [UNESP]; Lima, Betânia Moreira Chaves; Arcieri, Renato Moreira [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2014)
Fluoridation of water for human consumption is a method of caries prevention that brings great social benefit, if kept at optimal levels. The increase in the production of bottled water emphasizes the need to verify whether fluoride presence in these waters occurs in sufficient quantity to prevent decay, or if it represents a significant risk of fluorosis. Objective: to compare the concentrations of fluoride present in bottled water to those declared on the labels, and to make a critical analysis of legal norms on the subject. Materials and method: this was a cross-sectional study, through which 22 samples of bottled water sold in state of Ceará, Brazil, were analyzed. Analyses were performed in duplicate by the electrometric method, and results were compared to those printed on the labels. Detailed searches by laws, resolutions, ordinances, and other official documents in force, related to the topic were performed. Results: the fluoride concentrations found ranged from 0.01 to 0.36 mgF/l. Although 72.7% of the samples were classified as fluoridated, the fluoride concentrations observed were shown to be insufficient for caries prevention. As for the rules, situations where they are not clear or even divergent were found. Conclusion: the current legislation on the subject requires updates to become more objective and to create new criteria on the use of the term “fluoridated water”.

A fluoretação das águas para consumo humano é um método de prevenção da cárie que traz grande benefí- cio social, se for mantida em teores ideais. Com o aumento da produção de águas envasadas, acentua-se a necessidade de verificar se a presença de flúor nessas águas ocorre em quantidade suficiente para prevenir a cárie, ou ainda se representa risco significativo de fluorose. Objetivo: comparar as concentrações de flúor presentes em águas envasadas com aquelas declaradas nos rótulos das embalagens, e fazer uma análise crítica das normas legais sobre o tema. Materiais e método: tratou- -se de um estudo transversal, por meio do qual foram analisadas 22 amostras de águas envasadas comercializadas no estado do Ceará. As análises foram realizadas em duplicata, por meio do método eletrométrico, e os resultados obtidos foram comparados àqueles impressos nos rótulos das embalagens. Foram feitas buscas minuciosas por leis, resoluções, portarias, e outros documentos oficiais em vigor relacionados ao tema. Resultados: as concentrações de flúor encontradas variaram de 0,01 a 0,36 mgF/l. Apesar de 72,7% das amostras terem sido classificadas como fluoretadas, as concentrações de flúor observadas mostraram-se insuficientes para a prevenção da cárie. Quanto às normas, foram encontradas situações, em que essas não são claras, ou até mesmo divergentes. Considerações finais: a legislação vigente sobre o assunto necessita de atualizações para se tornar mais objetiva e para criar novos critérios sobre o uso da expressão “água fluoretada”.
Fluoride concentration in bottled waters: laboratory analysis and related legislation
Keywords: Bottled water; Fluorides; Health legislation; Product labeling; Água envasada; Fluoretos; Legislação sanitária; Rotulagem de produtos